Pemanfaatan sampah styrofoam untuk pembuatan lem lateks dalam upaya mengurangi limbah styrofoam di TPA Muara Fajar Timur Kecamatan Rumbai Pekanbaru - Desi Heltina; Amun Amri; Panca Setia Utama; Aman Aman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Various types of waste are found in TPA Muara Fajar Timur, Rumbai District, Pekanbaru. One of the waste that does not decompose is styrofoam. If styrofoam is not handled seriously, it will have an impact on the environment and endanger the surrounding community. Styrofoam waste contains polystyrene foam which contains hazardous materials for health and the environment. For this reason, efforts should be made to handle the styrofoam waste, namely by recycling styrofoam into useful and economical products. One of the uses of Styrofoam waste is making latex glue. Latex glue is a product that is widely used by the community so that if it is produced it will be able to meet the needs both for themselves and for the needs of the community. Latex glue is made from styrofoam by adding toluene and surfactants (sodium lauryl sulfate / SLS) or by adding gasoline to Styrofoam.The results obtained were that the community could understand and be able to make latex glue. The results of the success questionnaire show the high interest and benefits of this activity. This shows that this activity has been successfully implemented in Muara Fajar Timur Village, Rumbai District, Pekanbaru.